Capturing Architecture in Words - Coop Himmelblau (Oz, 1987)
Open architecture. How or who or what is that? Or rather, how should we think, plan, build in a world which is daily becoming more tattered? Should we fear these tatters, suppress them and flee into the safe world of architecture?